Training and environmental education. An integrated experience of learning based on territorial problems - Raimondo, Ana María; Gutierrez Pérez, José; Perales Palacios, Francisco Javier (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
Human resources training in environment university careers is relatively new in Argentina. It can be said that the offers start at the early ’90s, so nascent, then strengthened from the beginning of the XXI century. The present case corresponds to one of those degrees called Environmental Management, which belongs to the Faculty of Humanities and Social Sciences, National University of Patagonia San Juan Bosco. More than a decade after its creation, we are showing here some results and methodologies including in one of its subject entitled: Introduction to Environmental Issues.